Strategies of edition boards activity with readers of belles-lettres journals in 1930s (a case of magazines «Siberian Lights» and «The Future Siberia») - E. V. Evdokimova (Библиосфера, 2015)
The paper examines the basic publishing strategies of editorial boards of Siberian belles-lettres journals in the 1930s. Editorial staff activity of magazines in West and East Siberia is analyzed evidently for periodicals «Siberian Lights» and «The Future Siberia», the main forms of editor activity to promote editions to readership are identified. An attempt to classify the publishing strategies carried out by the magazine editorial boards is made. The strategies of personnel policy are considered as joining the best writers in the region around the journal, the use of a periodical format as an educational base to train a new type of writers, holding literary competitions. Strategies related to the content model of magazines include: focusing on regional issues, introduction newspaper elements to the editions conceptual model, boundaries blurring between the central and provincial literature. The strategy of mutual communication is understood as publishing readers' letters and manuscripts, critical remarks addressed to the editorial board. The particular importance for the editorial policy of Siberian belles-lettres journals is a strategy of cooperation between prints and media promoting them.